2019
DOI: 10.1038/s41467-019-12763-9
|View full text |Cite
|
Sign up to set email alerts
|

Unstable TTTTA/TTTCA expansions in MARCH6 are associated with Familial Adult Myoclonic Epilepsy type 3

Abstract: Familial Adult Myoclonic Epilepsy (FAME) is a genetically heterogeneous disorder characterized by cortical tremor and seizures. Intronic TTTTA/TTTCA repeat expansions in SAMD12 (FAME1) are the main cause of FAME in Asia. Using genome sequencing and repeat-primed PCR, we identify another site of this repeat expansion, in MARCH6 (FAME3) in four European families. Analysis of single DNA molecules with nanopore sequencing and molecular combing show that expansions range from 3.3 to 14 kb on average. However, we ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 46 publications
4
138
0
Order By: Relevance
“…First, the number of inherited repeats typically positively correlates with disease severity and negatively correlates with age of onset. Diseases with strong correlations between the number of repeats and age of onset are SCA7 (16,17), SCA3 (18), SCA2 (19 -21), SCA37 (22), HD (23)(24)(25)(26), DM1 (27,28), dentatorubral-pallidoluysian atrophy (DRPLA) (29,30), X-linked dystonia parkinsonism (XDP) (31), familial adult myoclonic epilepsy 3 (FAME3) (32), and Friedreich's ataxia (FRDA) (33,34). For some disorders, the correlation between the number of repeats and symptom manifestation is less clear, although there typically is a marginally significant trend (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the number of inherited repeats typically positively correlates with disease severity and negatively correlates with age of onset. Diseases with strong correlations between the number of repeats and age of onset are SCA7 (16,17), SCA3 (18), SCA2 (19 -21), SCA37 (22), HD (23)(24)(25)(26), DM1 (27,28), dentatorubral-pallidoluysian atrophy (DRPLA) (29,30), X-linked dystonia parkinsonism (XDP) (31), familial adult myoclonic epilepsy 3 (FAME3) (32), and Friedreich's ataxia (FRDA) (33,34). For some disorders, the correlation between the number of repeats and symptom manifestation is less clear, although there typically is a marginally significant trend (35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…Sixth, the origin of expanded alleles varies across repeats. For example, single common ancestors had a pathogenic amplification of ATTCT repeats in SCA10 (55)(56)(57), CCTG repeats in DM2 (58), and TTTTA/TTTCA repeats in FAME3 (32). Contrastingly, de novo repeat expansions were reported for the CAG repeat in HD (59), the CGG repeat in fragile X syndrome (60), and the GCN repeat in hand-foot-genital (HFG) syndrome (61).…”
mentioning
confidence: 99%
“…Recent discoveries have highlighted the importance of complex pathogenic repeat expansions involving non-reference insertions (Sato et al 2009;Seixas et al 2017;Ishiura et al 2018;Corbett et al 2019;Florian et al 2019;Yeetong et al 2019) . EHdn is currently the only method capable of discovering these expansions from BAM or CRAM files without the need for re-alignment of the supporting reads.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent discoveries have shown that many pathogenic repeats have complex structure and hence require more flexible methods. For instance: (a) REs causing spinocerebellar ataxia types 31 and 37, familial adult myoclonic epilepsy types 1, 2, 3, and 4, and Baratela-Scott syndrome (Sato et al 2009;Seixas et al 2017;Ishiura et al 2018;Corbett et al 2019;Florian et al 2019;Yeetong et al 2019;LaCroix et al 2019) occur within an inserted sequence relative to the reference; (b) expanded repeats recently shown to cause spinocerebellar ataxia, familial adult myoclonic epilepsy, and cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome have different composition relative to the reference STR (Sato et al 2009;Seixas et al 2017;Ishiura et al 2018;Corbett et al 2019;Florian et al 2019;Yeetong et al 2019) ; (c) Unverricht-Lundborg disease, a type of progressive myoclonus epilepsy, is caused by an expansion of a dodecamer (12-mer) repeat (Lalioti et al 1997) . None of the existing methods are capable of discovering all of these REs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to triplet repeats, pathogenic expansions of quintuplet repeat loci (represented as AAAAT in hg38) are associated with myoclonic epilepsies [14-16]. In 2018 and 2019, five AAAAT repeat loci were reported [14-16] in addition to BEAN1 which causes spinocerebellar ataxia 31 (MIM#117210) [17].…”
Section: Main Textmentioning
confidence: 99%